Financial Performance Analysis of Location, Rental Rate and Parking Revenue on Shopping Centers - Magdalena, Rita (Journal of Accounting and Business Education, 2017)
This study aims to determine the influence of location, rental rates, as well as parking revenues to the shopping centers financial performance as measured by proxy Return on Investment (ROI) in the city of Surabaya and Sidoarjo. In theory, this study aims to obtain empirical evidence over bid rent theory first proposed by ThÃ¼nen (1826) and the central location theory proposed by Christaller (1933) so as to benefit the investors, managers, and academics. This study uses secondary data sources. The analysis tool used is regression. Hypothesis testing results show that the strategic location of the shopping center increased financial performance, measured by using a proxy ROI (Return on Investment), while the price of rental and parking revenues shopping center does not have a significant impact on the financial performance. This supported the theory of transaction cost that every financial transaction must consider the cost factor that can lead to lower financial ratios, in addition to the queuing theory, which considers that any value of investment made to reduce queues should consider the return on investment along with factors of customer satisfaction and reducing the volume of the queue. The test results cluster analysis showed that the shopping centers located in residential centers have higher rental rates and earn higher parking revenues when compared with the shopping center located in the downtown area.Keywords: shopping centers, locations, rental rates, parking income, return on investment, financial performance